Foreign Direct Investment and Poverty in Nigeria - Udoinyang, Nathan; Umoh, Salamat Amos (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
Using yearly data series spanning 41 years, from 1981 to 2021, the research empirically evaluates the influence of FDI on poverty in Nigeria. The study's dependent variable was the poverty rate (PVT), while the independent variables were foreign direct investment (FDI) into agriculture (FDI), manufacturing (FDIM), services (FDIS), trade openness (OPN), and exchange rate (EXR). Statistical tools such as descriptive analysis, unit root testing, and ECM modelling were used to assess data that was retrieved from secondary sources. Foreign Direct Investment (FDI) in the agriculture sector decreases the poverty rate, FDIM in the manufacturing sector increases the poverty rate, FDIS in the service sector increases the poverty rate, OPN decreases the poverty rate, and EXR increases the poverty rate in Nigeria, according to the ECM. Foreign direct investment (FDI) did not alleviate poverty in Nigeria during the research period, the study found. The research concludes that foreign direct investment (FDI) may help Nigeria's economy expand and alleviate poverty if the government takes steps to attract FDI, such as lowering taxes, subsidizing infrastructure, and eliminating import duties